COMPUTED TOMOGRAPHY PARAMETERS OF CENTRAL PART OF LATERAL VENTRICLE OF THE BRAIN IN PODILLYA YOUNG MEN AND WOMEN WITH DIFFERENT SOMATOTYPES - Shevchuk, Yu.H. (World of Medicine and Biology, 2015)
In apparently healthy boys and girls of various somatotypes from Podillya features of computed tomographic parameters of the central part of the lateral ventricles of the brain were defined. The value of the distance from the central part of the right lateral ventricle and its index in girls with an average intermediate somatotype, the value of the distance from the central part of the left lateral ventricle in girls mesomorph and with a medium intermediate somatotype and value index of the central part of the left lateral ventricle in girls mesomorph significantly lower compared to girls endo-mesomorph. In boys with an average intermediate somatotype only value of the index of central part of the left lateral ventricle has a tendency to larger values compared to boys ectomorph. The rest of the parameters of the central part of the lateral ventricles of the brain in both boys and girls with different somatotypes had no significant or trends to differences of indicators.